Has economic freedom foster bank performance? panel evidence from China - Sufian, Fadzlan; Habibullah, Muzafar Shah (Routledge, 2010)
The impact of economic freedom on the wellbeing of the economy has been widely documented. Noticeably absent in literature is the empirical evidence on the impact of economic freedom on the banking sector. The present paper employs data on the Chinese banking sector and provides for the first time empirical evidence on the impact of economic freedom. We find evidence supporting greater freedom for entrepreneurs to start businesses. Interestingly, the impact of monetary freedom seems to be detrimental on the level of profitability of banks operating in the Chinese banking sector, providing support to the benefits of government interventions.